Fluoxetine affects cytosolic cAMP, ATP, Ca2+ responses to forskolin, and survival of human ovarian granulosa tumor COV434 cells - Thi Mong Diep Nguyen; Danièle Klett; Yves Combarnous (My University, 2021)
Fluoxetine affects cytosolic cAMP, ATP, Ca2+ responses to forskolin, and survival of human ovarian granulosa tumor COV434 cells
Keywords: Fluoxetine; Tế bào COV434; Đáp ứng tín hiệu tế bào